Performance monitoring and evaluation of water environment treatment PPP projects with multi-source heterogeneous information - Su, Limin; Cao, Yongchao (Frontiers in Environmental Science, 2022)
Effective measuring and monitoring the services quality from the private sector in the terms of performance in water environment treatment public-private partnership projects (WETPs-PPP) is one of the keys to the success of the projects. Based on the deficiencies of performance monitoring and evaluation theory and the specific characteristics of WETPs-PPP, this study aims to develop a performance monitoring and evaluation model for WETPs-PPP. First, through literature analysis, a performance monitoring and evaluation index system of WETPs-PPP is constructed from eight dimensions including River embankment, Bridges, River water, Environment, Garden facilities, Garden Plants, Special Purpose Vehicle, Hydraulic structure and Public Satisfaction. Second, combining the adaptive weighted fusion algorithm and Intuitionistic Fuzzy (IF) average operators, the multi-source, multi- dimensional and multi-spatio-temporal data are aggregated. Third, to improve the robust of the performance monitoring results, the MULTIMOORA evaluation method with defuzzification procedure under IF environment is developed to carry out performance monitoring and evaluation for WETPs-PPP. Finally, a water environment treatment and ecological restoration project is taken as an example to illustrate the feasibility and effectiveness of the proposed theoretical model.